ナンキョク サン クマムシ Macrobiotus harmsworthi ト センチュウ Plectus antarcticus ノ タイトウ セイ - 菅原, 裕規; スガワラ, ヒロミ; 丹野, 晧三; タンノ, コウゾウ; 大山, 佳邦; オオヤマ, ヨシクニ; 福田, 弘巳; フクダ, ヒロミ; Sugawara, Hiromi; Tanno, Kouzou; Ohyama, Yoshikuni; Fukuda, Hiromi (1990)
P(論文) 東南極に位置するラングホブデ露岩域の雪鳥沢で採取した蘚類を-20℃で冷凍保存して日本に持ち帰り(約10ヵ月にわたる保存中の生存率はクマムシで49%, センチュウで58%), その中から抽出したクマムシ(Macrobiotus harmsworthi J. MURRAY)およびセンチュウ(Plectus antarcticus DE MAN)を-10℃から-80℃まで冷却し, -10℃, -18℃, -32℃, -40℃, -80℃における耐凍性を調べた。その際, -10℃から-40℃までは, 自然条件下での蘚類内温度の変化に近似させるため極めて遅い速度で冷却し(2℃/日), -40℃から-80℃にかけてはやや急速に冷却した(20℃/時)。耐凍性の目安として, 融解して2時間, 4時間, 2週間および5週間後の活動個体の割合(RA値)を求めた。クマムシの耐凍性は非常に高く, -80℃まで冷却された個体のほとんどが乾眠状態で生存し, RA値は融解2時間後で100%, 5週間後でも86%に達した。-40℃, -32℃まで冷却された個体もほぼ同様の傾向を示したが, -18℃と-10℃までしか冷却されなかった個体ではRA値がやや低く, 融解2時間後でそれぞれ75%と70%, 5週間後で40%と60%にすぎなかった。センチュウの耐凍性も高く, 融解4時間後におけるRA値は, -32℃冷却個体における46%を除くと, 79%(-80℃冷却)～100%(-10℃冷却)に達した。しかし, 以後急速に死亡個体が増加し, 2週間後のRA値は0%(-10℃, -18℃冷却), 11%(-32℃), 5%(-40℃), 3%(-80℃)にすぎず, 5週間後には全個体死亡した。以上のように, クマムシ, センチュウともに, 高温冷却個体より低温冷却個体の方がやや高い耐凍性を示しているが, この高い耐凍性が極地環境においてこれらの種の生存を可能としているものと考えられる。 In early January of 1988,we collected mosses in the ice-free Yukidori Valley area of Langhovde, near Syowa Station in East Antarctica. The mosses were stored at -20℃ and shipped to Japan. After ten months of storage, Macrobiotus harmsworthi J. MURRAY (Tardigrada) and Plectus antarcticus DE MAN (Nematoda) were extracted from these mosses to test their freezing-tolerance. These extracted samples were cooled from -10℃ to -40℃ at -2℃/day, as slow as cooling conditions similar to the natural habitats, then down to -80℃ rapidly at -20℃/hr. At -10℃, -18℃, -32℃, -40℃ and -80℃ in the course of cooling, some individuals were taken out of the freezer and cultured at 0℃. The ratio of active individuals (RA) was assessed for the periods of two hours, four hours, two weeks and five weeks after thawing. Most individuals of M. harmsworthi were dormant at low temperatures. RA of the individuals cooled to temperatures below -32℃ ranged from 80 to 100% in two hours after thawing. The values remained as high as 75–86% even after five weeks. The individuals cooled to -10℃ or -18℃ showed a smaller RA which was about 70% two hours later and only about 50% five weeks later. In P. antarcticus the RA values ...